Application of Integers in Vernam Cipher Cryptography (One Time Pad) - Parasian D.P Silitonga; Sorang Pakpahan (INFOKUM, 2021)
Today, the effective security of a system is indispensable for daily business activities. A secure system can provide a high level of trust to users so that it can add value and usability to the system itself. Users will feel comfortable and safe when dealing with systems that can secure user data from attackers. There are several ways to secure data through a channel, one of which is cryptography. In cryptography, highly confidential data will be disguised in such a way that even if the data can be read it cannot be understood by unauthorized parties. Data that will be sent and has not been encrypted is known as plaintext, and after being disguised by an encoding method, this plaintext will turn into ciphertext.